The effect of trichostatin-A and tumor necrosis factor on expression of splice variants of the MaxiK and L-type channels in human myometrium - Waite, Sarah L.; Gandhi, Saurabh V.; Khan, Raheela N.; Chapman, Neil R. (Frontiers in Physiology, 2014)
The onset of human parturition is associated with up-regulation of pro-inflammatory cytokines including tumor necrosis factor (TNF) as well as changes in ion flux, principally Ca2+ and K+, across the myometrial myocytes membrane. Elevation of intra-cellular Ca2+ from the sarcoplasmic reticulum opens L-type Ca2+ channels (LTCCs); in turn this increased calcium level activates MaxiK channels leading to relaxation. While the nature of how this cross-talk is governed remains unclear, our previous work demonstrated that the pro-inflammatory cytokine, TNF, and the histone deacetylase inhibitor, Trichostatin-A (TSA), exerted opposing effects on the expression of the pro-quiescent Gαs gene in human myometrial cells. Consequently, in this study we demonstrate that the different channel splice variants for both MaxiK and LTCC are expressed in primary myometrial myocytes. MaxiK mRNA expression was sensitive to TSA stimulation, this causing repression of the M1, M3, and M4 splice variants. A small but not statistically significantly increase in MaxiK expression was also seen in response to TNF. In contrast to this, expression of LTCC splice variants was seen to be influenced by both TNF and TSA. TNF induced overall increase in total LTCC expression while TSA stimulated a dual effect: causing induction of LTCC exon 8 expression but repressing expression of other LTCC splice variants including that encoding exons 30, 31, 33, and 34, exons 30–34 and exons 40–43. The significance of these observations is discussed herein.